Nutrient composition and in vitro fermentation characteristics of common vegetable peels as livestock feed - Abigail, G.B; Muhammad, A.I.; Hemly, N.I.M; Zainudin, N.N; Khairul, A.B; Samsudin, A.A. (Malaysian Society of Animal Production, 2024)
The study evaluated the nutritional composition and in vitro rumen fermentation characteristics of four common vegetable peels: cucumber, carrot, potato, and ginger as potential feed resources for livestock feed. The chemical composition and in vitro gas production, dry matter digestibility, and volatile fatty acid profiles of these peels were assessed in a complete randomized design (CRD). The results showed That cucumber peels exhibited higher (P < 0.0001) organic matter (OM), crude protein (CP), acid detergent fibre (ADF), and acid detergent lignin (ADL) content; 24.81%, 21.37%, 44.50% and 44.50%, respectively, whereas lowest DM content (5.50%). Carrot peels had the lowest CP (5.61%) and NDF (34.30%) content. Potato peels were characterized by higher DM (14.56%) content and lower OM (7.95%), ADF (25.68%), and ADL (26.67%) content. The ginger peels had the highest (P < 0.0001) NDF (86.64%) content. In vitro gas production studies revealed carrot peels had the highest cumulative gas production, while the lowest in ginger peels. Similarly, carrot peels exhibited the highest (P < 0.0001) in vitro dry matter digestibility (IVDMD) and lowest in vitro neutral detergent fibre digestibility (IVNDFD). The potato peel volatile fatty acid (VFA) profile produced the highest concentrations of acetic, propionic, butyric acids and total VFA. In conclusion, cucumber, carrot, and potato peels have the potential to be used as potential feed resources for livestock. Further research (in vivo) is required to assess their effects on animal performance and health.